Peningkatan Efisiensi Kinerja Permasalahan Supplier Wismilak Group - Yan Pujianto Sanjaya; Kriswanto Widiawan (Jurnal Titra, 2017)
Wismilak Group is one of the companies that produce consumer good in Surabaya. Cleaning supplier is needed because there are too many suppliers’ database and some of the suppliers are inactive. The company also wants to improve efficiency by making contract with several suppliers. Performance efficiency will decrease the number of suppliers by 113 suppliers. Rationalization of purchases by making contract also succeeded in reducing the average lead time of making purchase orders up to 34%. Purchase by contract also resulted in cost efficiency in the form of saving to P/L of 4% and saving to budget of 10%. Cost efficiency calculations for the purchase of printed goods are done as supporting evidence. The rationalization of purchases on printed goods will result in a cost efficiency of 19%. Rationalization of purchase can cause problems of delays in the supply of goods. The suggestion given is the calculation of safety stock and reorder point for the purchase of printed goods.